The Planck Length , Newton Gravitational Constant and Gravity Constant - Giorgallides, Marcos (IJRDO - Journal of Mechanical And Civil Engineering, 2019)
In [39] was shown that Universe is consisted of two fundamental elements ,that of Space i.e. A point without existence and another point B without existence also but not coinciding because if differently should not be a Two-Points-Vector which is property of point. Point B is the Anti-Space , and this to exist at a distance AB from point A is done a motion . This motion in Mechanics is called Energy and , In order that Motion is Conserved as Displacement in all directions , then this Displacement must be kept, Quantized, in a Finite Space differently is annihilated .In Mechanics the only-possible motion in a Finite Space , is the Periodic excitation [↔] and the Revolving motion [ (+) ↻↺ (-) ] . Revolving motion may exist between Space (+) and Anti-Space (-) so the Revolving of Two-Points A(+) and B(-) consist the Material-Point as Segment ,magnitude |AB|, and as Vector, direction